Two views on political lesser evil - Francisco Garcia Gibson (Filosofia Unisinos)
In this article I argue that doing the lesser evil in politics is always permitted and even required. I call this view “pragmatism”. I defend it against “purism”, which claims that it is never permissible to do (the lesser) evil. I reject three arguments for purism, which are based on Alan Gewirth’s principle of intervening action, on an alleged epistemic difference between doing and allowing evil, and on rule-consequentialism. I also address Terrance McConnell’s and Thomas Hill Jr.’s attempts to constrain pragmatism by claiming that doing the lesser evil is not always permitted or required. Although those constraints may apply to most spheres of action, I contend that they do not apply to political action.